Job stress: an analysis at coordinator level in UiTM Johor - Elias, Suhaidi; Ismail, Noriah (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2008)
This study analyzes the factors which contribute to stress in a coordinator's work. A total of 33 coordinators and ex-coordinators from UiTM Johor were selected to be the respondents of the study. A set of questionnaires was designed to gain the primary data from the respondents. The overall findings of the study indicate that job stress is prevalent among the coordinators as 80% of them would refuse to continue serving as a coordinator should they be asked to renew their term. The study also discovered that the two main causes of job stress among the coordinators are in terms of the 'administration work domain' they are involved in as well as the 'system used' by the university such as the ICRESS and ISIS which does not often run smoothly. The study also provides some suggestions to reduce the level of stress among the coordinators and suggestions for future research.